In vitro phase I metabolism study of diuretics clopamide by LC-MS/MS - FARZANA BINTE RAFIQUE; Muresan Anca Raluca; RAHAMAN KHANDOKER ASIQUR; Ki Hun Kim; Lee Kang Mi; Hophil Min; Kim Ho Jun; Changmin Sung; SON Junghyun; Lee Jae Ick; Kwon, Oh-Seung (Proceedings of the 38th Cologne Workshop, 2020)
Diuretics are often illegally used in different kind of sports discipline, and clopamide is included in the list of prohibited substances of World Anti-Doping Agency. The objective of this study was to investigate clopamide metabolites in vitro enzyme system in both negative ionization ([M-H]-, m/z 344) and positive ionization ([M+H] +, m/z 346) since its metabolism study was not reported yet. In this study, the phase I metabolites were generated through an in-vitro enzyme system with rat liver microsome, and identified by using both negative and positive ionization modes of an ultra high-performance liquid chromatography/Orbitrap mass spectrometer (Q-Exactive). A full scan and dd-MS/MS modes were used to obtain structural information of the metabolites. We have characterized 3 mono-hydroxylated ([M-H+16]-, m/z 360) metabolites and 2 dehydrogenated metabolites ([M-H-2]-, m/z 342) at collision energy of 40 eV in negative mode. In case of positive ionization, 3 mono-hydroxylated metabolites ([M+H+16] +, m/z 362), and 2 dehydrogenated metabolites ([M+H-2]-, m/z 344) were found at collision energy of 35 eV, based on their structures and mass spectra. These metabolites could be useful for further in vivo metabolites identification with the purpose of anti-doping analysis. The further in-vitro phase II and in-vivo studies are progressing to identify more metabolites as potential biomarkers for anti-doping analysis.
Keywords: Diurectics; null; Clopamide; null; Metabolites; null; LC-MS/MS